Posted by upbeat on Tuesday, July 20, 2010 at 12:35pm.
solve by the substitution method
the solution is (___,___)
- substitution method - Henry, Tuesday, July 20, 2010 at 3:38pm
1. 2m + n = 9
m - 6n = 50
Using Eq.1, solve for n:
n = 9 - 2m
Substitute 9 - 2m for n in Eq. 2:
m -6(9 -2m) = 50
Solve for m:
m - 54 + 12m = 50
m = 8
Substitute 8 for m in Eq. 1:
2(8) + n = 9
n = -7.
Solution: m = 8, and n = -7.
- substitution method - dawn, Monday, November 8, 2010 at 11:52pm
Answer This Question
More Related Questions
- substitution method - solve using the substitution method 8x+6y=8 -9x+y=22 The ...
- substitution method - solve using the substitution method 6x+2y=-14 -5x+y=25 The...
- substitution method - solve using the substitution method 8x -9y= -95 5x+64=y ...
- Elimination Method Help - solve by the elimination method 5x+5y= -7 7x-3y=19 The...
- Algebra 1 - bobpursey, In this problem you helped me with earlier: Solve using ...
- Substitution Method-Plz help - Use the Substitution method to solve the system ...
- substitution method - Solve by substitution method please help me solve this. I ...
- Algebra 116 - 1. The perimeter of a rectangle is 126 m. The length is 6 m more ...
- Linear Equations - Can you please help solve this equation using the ...
- calculus - Leave any unneeded answer spaces blank. [Hint: use synthetic division...